2015
DOI: 10.1128/jvi.02830-14
|View full text |Cite
|
Sign up to set email alerts
|

GBF1- and ACBD3-Independent Recruitment of PI4KIIIβ to Replication Sites by Rhinovirus 3A Proteins

Abstract: c PI4KIII␤ recruitment to Golgi membranes relies on GBF1/Arf and ACBD3. Enteroviruses such as poliovirus and coxsackievirus recruit PI4KIII␤ to their replication sites via their 3A proteins. Here, we show that human rhinovirus (HRV) 3A also recruited PI4KIII␤ to replication sites. Unlike other enterovirus 3A proteins, HRV 3A failed to bind GBF1. Although HRV 3A was previously shown to interact with ACBD3, our data suggest that PI4KIII␤ recruitment occurred independently of both GBF1 and ACBD3. E nteroviruses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 18 publications
(34 reference statements)
1
57
0
Order By: Relevance
“…Work on Aichi virus led to conclusion that Golgi adaptor protein ACBD3 is the cellular mediator of interaction between 3A protein and PI4K IIIβ [74,104] but details regarding the recruitment of the IIIβ enzyme by enteroviruses are conflicting. siRNA against ACBD3 was reported to both lower and increase the replication of the poliovirus [105,107] but not of the CVB3 or rhinovirus [108,109], which is surprising as the 3A proteins of these enteroviruses are rather similar and their 3A proteins interact with ACBD3 [105]. The level of knock-down, siRNA off-target effects or the viral strand may play an important role but perhaps an important piece of the puzzle is still missing.…”
Section: Pi4ks In Health and Diseasementioning
confidence: 89%
“…Work on Aichi virus led to conclusion that Golgi adaptor protein ACBD3 is the cellular mediator of interaction between 3A protein and PI4K IIIβ [74,104] but details regarding the recruitment of the IIIβ enzyme by enteroviruses are conflicting. siRNA against ACBD3 was reported to both lower and increase the replication of the poliovirus [105,107] but not of the CVB3 or rhinovirus [108,109], which is surprising as the 3A proteins of these enteroviruses are rather similar and their 3A proteins interact with ACBD3 [105]. The level of knock-down, siRNA off-target effects or the viral strand may play an important role but perhaps an important piece of the puzzle is still missing.…”
Section: Pi4ks In Health and Diseasementioning
confidence: 89%
“…It has been demonstrated that transient expression of an A16 3A protein by transfection, can lead to disruption of the Golgi structure and inhibition of cellular protein secretion (Mousnier et al, 2014). Replication of this virus depends on GBF1 and PI4KIIIβ but not on ACBD3, and moreover, PI4KIIIβ recruitment to viral replication sites is mediated by the 3A protein (Dorobantu et al, 2015). Certain single-point mutations in the 3A protein of B14 and some other related picornaviruses, likewise confer resistance to some antiviral compounds (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…HNF4 ␣ ( 11 ), sterol regulatory element-binding protein (SREBP) 1 ( 12 ), plant AtEBP ( 13 ), and several viral proteins ( 3,(14)(15)(16)(17)(18). Plant ACBP members are also implicated in a multitude of function such as embryogenesis and resistance to various stresses ( 4,5,11 ).…”
mentioning
confidence: 99%